PROSTITUTION IN THE STUDY OF PHILOSOPHY, ETHICS, AND LAW IN INDONESIA - krismono irwanto; Richard Kennedy Kennedy (Journal Philosophy of Law, 2020)
Prostitution is a crime that has been known since the beginning of human existence. Many laws have been created in such a way to control, reduce and even abolish this crime. However, because prostitution is a crime related to basic human instincts that come out of the value system, no law has been able to stop it from century to century. This prostitution even is incarnated in various new modes and forms. The problem then is why the law seems powerless in controlling, reducing, and even eliminating this crime. A logical explanation is needed to answer this question than just guessing the correlation between basic human instincts and the decline of moral values. The values that have been built since the law was formed are, in fact, unable to teach humans to live in that order. Studying law in an ontological and epistemological context is expected to find the form of its failure to control this crime. This study also examines and tries to see how values can be applied in human life and improve their quality. This study is expected to find concrete answers on how the law should be able to organize its rules so that it has sufficient coercive power to control any modes and forms that arise in the context of this prostitution. The approach used in reviewing the law is also expected to answer any difficulties that hinder its enforcement. Thus, the law becomes powerless to deal with such complex prostitution problems.